2017
DOI: 10.1080/09603123.2017.1282605
|View full text |Cite
|
Sign up to set email alerts
|

Affective outcomes during and after high-intensity exercise in outdoor green and indoor gym settings

Abstract: Citation: TURNER, T.L. and STEVINSON, C., 2017. Affective outcomes during and after high-intensity exercise in outdoor green and indoor gym settings. International Journal of Environmental Health Research, 27 (2), pp. 106-116. Methods:This study compared the psychological effects of high intensity exercise in outdoor green and indoor gym settings in 22 adult runners using a randomized repeated measures design. Affect and perceived exertion were assessed before, during, and after a 6000m run with the second ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 57 publications
1
34
0
Order By: Relevance
“…Notably, Jones and Doust [2] found that V O 2 could be matched between overground and motorised treadmill conditions by adjusting the treadmill grade to 1%. As a result, many researchers adjust the treadmill grade to 1% [12][13][14][15][16], despite not all studies supporting this practice [5,12]. Using a treadmill grade such as 1% might be particularly important at faster running speeds, which tend to demonstrate greater air resistance during overground running larger systematic review project comparing overground and treadmill running across a broader range of outcome measures (Registration number CRD42017074640).…”
Section: Registration Of Systematic Review Protocolmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, Jones and Doust [2] found that V O 2 could be matched between overground and motorised treadmill conditions by adjusting the treadmill grade to 1%. As a result, many researchers adjust the treadmill grade to 1% [12][13][14][15][16], despite not all studies supporting this practice [5,12]. Using a treadmill grade such as 1% might be particularly important at faster running speeds, which tend to demonstrate greater air resistance during overground running larger systematic review project comparing overground and treadmill running across a broader range of outcome measures (Registration number CRD42017074640).…”
Section: Registration Of Systematic Review Protocolmentioning
confidence: 99%
“…This review contained a total of 468 total participants (350 males, 102 females, 16 not specified). Of the 34 studies included in the review, 23 studies [1, 2, 6, 8-10, 14, 16-19, 21, 29, 30, 32, 34, 35, 37, 38, 40-43] included only male participants, two studies [12,36] did not specify participant sex, and nine studies [5,11,13,15,20,31,33,39,44] included a mix of male and female participants. Twenty-one studies recruited only runners and typically described the runners in their studies as 'trained', 'distance' or 'recreational' runners.…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations